Chinese herbs: treasure troves for the discovery of environmentally friendly promoters for methane hydrate formation. Issue 12 (2nd November 2020) - Wang, Suying; Zeng, Yanxian; Cai, Yuanhao; Niu, Xiaochun; Zhu, Zhengmei; Lei, Dongjun; Wang, Weixing
Abstract : Chinese herbs can "cure" the sluggish kinetics of methane hydrate formation under static conditions. Abstract : Chinese herbs are rich resources for the discovery of new environmentally friendly promoters for methane hydrate formation. We demonstrated that 20 out of 300 kinds of Chinese herbs were highly effective in promoting methane hydrate formation. Moreover, a more effective promoter than sodium dodecyl sulfate (SDS, the benchmark promoter), magnesium baicalin derived from Scutellariae Radix (Huangqin) was identified.